Effect of Feeding Chaya (Cnidoscolus chayamansa) Leaf on Nutrient Digestibility and Blood Profiles in Growing Dairy Cattle - Wongnhor, Morrakod; Khonyoung, Duddoa (Journal of Mahanakorn Veterinary Medicine, 2022)
The aim of this study was to investigate the effect of feeding dried chaya (Cnidoscolus chayamansa) leaf on nutrient digestibility and blood profiles in growing dairy cattle. Four Holstein-Friesian growing heifers averaging 181.75 ± 42.74 kg of body weight and 300.75 ± 83.47 d of age were randomly assigned to a change over design in two periods with two treatments as follows: control group and replacing concentrate with 5% chaya leaf. The concentrate was given 0.75% of BW with fresh pangola grass as roughage. There were 17 d adaptation in each period, followed by 4 d measurement period for fecal sample collection. Blood collection was collected in each cow: pre and post-trial via jugular venipuncture. The result of this study revealed that cyanide content in dried chaya leaf was 97.2 ppm. Compared to control group, body weight gain, average daily gain, dry matter intake and G : F were not significantly different (P>0.05). There were no significant differences in dry matter and crude protein digestibility between groups. The 5% chaya leaf had no impact on PCV, RBC, hemoglobin, MCV, MCH and MCHC values. While lymphocytes of the cow fed 5% dried chaya leaf was significantly lower (P<0.05) than lymphocytes of the control group. Blood chemistry serum such as total protein, albumin, AST and ALT of 5% chaya leaf were not significantly different from the control group. This study indicates that the replacement of concentrate with 5% dried chaya leaf can be used as a feed ingredient since it has no effect on growth and health in growing dairy cattle.